Robust estimation of wages in small enterprises: the application to Poland's districts - Grażyna Dehnel; Łukasz Wawrowski (Statistics in Transition New Series, 2020)
The paper presents an empirical study designed to test a small area estimation method. The aim of the study is to apply a robust version of the Fay-Herriot model to the estimation of average wages in the small business sector. Unlike the classical Fay-Herriot model, its robust version makes it possible to meet the assumption of normality of random effects under the presence of outliers. Moreover, the use of this version of the Fay-Herriot model helps to improve the precision of estimates, especially in domains where samples are of small sizes. These alternative models are supplied with auxiliary variables. The study seeks to present the characteristics of and differences among small business units cross-classified by selected NACE sections and district units of the provinces of Mazowieckie and Wielkopolskie. It was carried out on the basis of data from a survey conducted by the Statistical Office in Poznan and from administrative registers. It is the first study which attempts to produce estimates of average wages for this sector of the national economy.
Keywords: C13; C51; M20; 519; dynamic model; Bayesian inference; CO2; climate change; energy